2007
DOI: 10.1590/s1807-76922007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalization and organizational long-term success

Abstract: Institutionalization processes have an ambivalent effect on organizational long-term success. Even though they foster organizational stability and permanence, they also bring about rigidity and resistance to change. As a result, successful organizations are likely to lose their competitive advantage over time. The paper addresses this issue through the investigation of the institutionalization processes of two long-lived companies: General Electric, a firm that has been a long-term success and its rival, Westi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
1
2
0
4
Order By: Relevance
“…One area where those responsible for developing strategies in relation to sustainable procurement can learn lessons relates to the management of innovation. Structural inertia in this area is overcome by systematic problem‐solving in areas including technology, administrative issues, inter‐organizational relationships, renewal of resources, sustained risk management and planned responses to the external environment (Fleck, 2007). For sustainable procurement, a key factor is the management of inter‐organizational relationships.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…One area where those responsible for developing strategies in relation to sustainable procurement can learn lessons relates to the management of innovation. Structural inertia in this area is overcome by systematic problem‐solving in areas including technology, administrative issues, inter‐organizational relationships, renewal of resources, sustained risk management and planned responses to the external environment (Fleck, 2007). For sustainable procurement, a key factor is the management of inter‐organizational relationships.…”
Section: Discussionsupporting
confidence: 87%
“…Experience of other industries suggests that structural inertia can be overcome. Fleck (2007) studied General Electric (GE), a long‐lived US electrical manufacturing company, and concluded that to neutralize structural inertia it institutionalized those practices that allowed renewal of routines and redefinition of its relationship with its environment.…”
Section: Discussionmentioning
confidence: 99%
“…Zucker (1977) afirma que a resistência à mudança é afetada pela institucionalização. A autora enfatiza que quanto mais elevado o grau de institucionalização, maior é a resistência à mudança, pois ela induz à estabilidade e à persistência em relação às formas e aos comportamentos estruturais (Fleck, 2007).…”
Section: Resistência à Mudança à Luz De Abordagens Psicanalíticasunclassified
“…Um foco importante dessas abordagens interpretativistas na teoria administrativa contemporânea é a aproximação entre nova teoria institucional e estudos em estratégia. As características e possibilidades dessa aproximação vêm sendo descritas na literatura recente (OLIVER, 1991;1997;INGRAM e SILVERMAN, 2002;MACHADO-DA-SILVA, 2003;CRUBELLATE, GRAVE e MENDES, 2004; SEIFERT e MACHADO- FLECK, 2007;VASCONCELOS, QUEIROZ e GOLDSZMIDT, 2007) que, em resumo, relaciona interesses de atores sociais, restrições e oportunidades institucionais e a estratégia organizacional (ou variáveis a ela pertinentes). O modo de explicação dessa inter-relação marca as diferentes formas pelas quais a nova teoria institucional vem sendo incorporada na discussão relativa à estratégia em organizações, com destaque para a vertente que explica o impacto do contexto institucional pela via da imersão social dos atores em redes sociais.…”
Section: Troduçãounclassified